1988
DOI: 10.1007/bf00425160
|View full text |Cite
|
Sign up to set email alerts
|

A second streptomycin resistance gene from Streptomyces griseus codes for streptomycin-3?-phosphotransferase

Abstract: Two genes, aphE and orf, coding for putative Mr 29,000 and Mr 31,000, proteins respectively, were identified in the nucleotide sequence of a 2.8 kbp DNA segment cloned from Streptomyces griseus N2-3-11. The aphE gene expressed streptomycin (SM) resistance and a SM phosphorylating enzyme in S. lividans strains. The two genes were found to be in opposite direction and seemed to share a common region of transcription termination. The aphE gene shows significant homology to the aph gene, encoding aminoglycoside 3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…Studies on antibiotic production, mostly in the actinomycetes, indicate that self-resistance to antibiotics is achieved by excluding the antibiotic from the environment of the sensitive target, by modifying or degrading the antibiotic (often by an enzyme in the biosynthetic pathway), or by modifying or replacing the target so that it is no longer antibiotic sensitive (10,16,22,23,34,35,45,46,(49)(50)(51)(52). Does the mechanism for ZmaR-based resistance fit one of these profiles?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on antibiotic production, mostly in the actinomycetes, indicate that self-resistance to antibiotics is achieved by excluding the antibiotic from the environment of the sensitive target, by modifying or degrading the antibiotic (often by an enzyme in the biosynthetic pathway), or by modifying or replacing the target so that it is no longer antibiotic sensitive (10,16,22,23,34,35,45,46,(49)(50)(51)(52). Does the mechanism for ZmaR-based resistance fit one of these profiles?…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of selfresistance fall into three general classes (10): (i) inactivation of the antibiotic by chemical modification (22,33,35); (ii) rapid efflux or sequestering of the antibiotic from the vicinity of the target site or the interior of the cell (45,51); and (iii) modification or replacement of the sensitive target site with an insensitive form (16,23,34,46). Genes encoding self-resistance are often clustered with genes encoding other functions required for antibiotic production, namely, biosynthetic enzymes, export pathways, and regulators of production.…”
mentioning
confidence: 99%
“…RT-PCR analysis of pkn5 at different developmental stages indicated that pkn5 is in fact a transcriptionally active gene in Chlamydia. We suggest that chlamydial Pkn5 is not a protein kinase but could be an aminoglycoside 3Ј phosphotransferase, phosphorylating nonprotein substrates such as antibiotics in order to neutralize their toxic properties (11,19). Further sequence analysis of Pkn1 and PknD indicated the presence of potential transmembrane domains at the N terminus of Pkn1 (amino acids 207 to 224) and PknD (amino acids 663 to 681).…”
Section: Discussionmentioning
confidence: 93%
“…Several other false-positive matches to non-PK sequences were also observed. These non-PK sequences were mostly antibiotic (e.g., aminoglycoside) phosphotransferase resistance genes that are distantly related to protein kinases (Brenner, 1987;Heinzel et al, 1988).…”
mentioning
confidence: 99%
“…When ORF186 and CEZK632-3 are multiply aligned with eukaryotic PK sequences, the ORF186 and CEZK632-3 sequences match the eukaryotic PK sequences within only 4 (regions 1, 11, VI, and VII) of the I 1 regions characteristically conserved within the catalytic domain of eukaryotic PKs (Hanks et al, 1988;Hanks & Quinn, 1991; alignment not shown). Because bacterial antibiotic phosphotransferase sequences share 127 these same domains with eukaryotic PKs (Brenner, 1987;Heinzel et al, 1988), the 7: acidophilum and C. elegans sequences most likely encode some type of phosphotransferase that is not a protein kinase, per se.…”
mentioning
confidence: 99%